EFEKTIVITAS DAN TANTANGAN PELAKSANAAN RESTORATIF JUSTICE DALAM KOMPONEN SISTEM PERADILAN PIDANA INDONESIA - m khalil ibrahim ali (Jurnal Hukum Lex Generalis, 2024)
Eglash explained that restorative justice is a form of constructive, creative and self-determining action that provides support and opportunities for group participation. One form of criminal law reform in Indonesia is the structuring of criminal law from the perspective and realization of thoroughness to justify or resolve the situation after a case or criminal justice process, which is known as restorative justice. Challenges are needed to provide answers to the direction and objectives of RJ implementation as well as see whether the implementation of RJ in Indonesia has been effective, and the circumstances in which law enforcement officers can use RJ in the Indonesian judicial context. From a policy perspective, there has been no comprehensive statement describing the effectiveness and challenges of the Indonesian criminal justice system.